KONSENTRASI GULA DAN SARI BUAH TERHADAP KUALITAS SIRUP BELIMBING WULUH (Averrhoa bilimbi L.) - Elpida Fitri; Noviar Harun; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to obtain the best concentration of sugar and the amount of fruit extracts in makingAverrhoa bilimbiL.syrup based on the quality of physical, chemical and organolepticresults test produced syrup. This research was conducted using a completely randomized design (CRD) with five treatments and three replications. The treatment in this study were GB1 : 50% sugar with 50% fruit ectracts(w/v), GB2: 55% sugar with 45% fruit extracts(w/v), GB3 : 60% sugar with 40% fruit extracts (w/v), GB4: 65% sugar with 35% fruit ectracts(w/v) andGB5: 70% sugar with 30% fruit extracts(w/v). Data obtained were treated by the analysis analysis of variance (ANOVA) followed by Duncan’s New Multiple RangeTest(DNMRT) the level 5%. Based on the research can be concluded that comparison Averrhoa bilimbiL. extract and sugar significantly affect on the value of pH, sucrose concentration, viscosity, color, aroma, taste descriptively but no significant effect on the color, aroma, taste and overall assessment basis hedonic. The best treatment that has fulfilled SNI syrup isGB5with a ratio of sugar and Averrhoa bilimbiL. Extract 70%: 30%. The result of syrup has a pH value of 4.32, sucrose concentration67.42%, viscosity 1708.33 cP with description color is brownish yellow, rather flavorful Averrhoa bilimbiL., sweet taste slightly sour and panelistsfavoredoverall. Keywords: syrup, sugar and Averrhoa bilimbiL.